Potyviral VPg and HC-Pro proteins and the cellular translation initiation factor eIF(iso)4E interact with exoribonuclease Rrp6 and a small a-heat shock protein - Freire, Miguel Angel (2014)
The helper-component proteinase (HC-Pro) of potyvirus is a multifunctional protein involved in many mechanisms of viral life cycle. In addition, HC-Pro protein was the first identified suppressor of RNA silencing in plants. However, the identities and functions of direct targets toward the pathways of RNA-silencing suppression mediated by HC-Pro are still to be determined. Here, a yeast two-hybrid search for potyviral HC-Pro interacting tobacco proteins was done to identify host partners and potential silencing suppressors. Two interacting cDNA clones were isolated. One of them encodes an Rrp6-like protein, a subunit of the exosome complex that belongs to the RNase D family of the DEDD superfamily of 3′–5′ hydrolytic exoribonucleases. The other clone codes for a small α-heat shock protein (α-Hsp). The interactions were validated by cross interaction assays with other potyviral HC-Pro proteins. Moreover, both identified clones also interacted with pathogenic viral protein-linked genomes (VPgs) and with translation eukaryotic initiation factors (iso) 4E (eIF(iso)4E) which are host determinants of resistance or susceptibility to potyvirus infections. All together, these findings emphasize the role of the potyviral HC-Pro and VPg proteins and the translation initiation factor eIF(iso)4E, as key players of the plant–virus interplay, where the exoribonuclease Rrp6 and a small α-heat shock protein appear as novel sharing targets.